10.3k views
1 vote
If f(x) = (x - 3)/(x + 4), find f -1(x).

User Shenglih
by
5.0k points

1 Answer

3 votes

Answer:

f^-1(x) = (4x +3)/(1 -x)

Explanation:

Solve for y:

f(y) = x

(y -3)/(y +4) = x

y -3 = xy +4x . . . . . . multiply by y+4

y -xy = 4x +3 . . . . . . add 3-xy

y(1 -x) = 4x +3 . . . . . factor out y

y = (4x +3)/(1 -x) . . . divide by the coefficient of y

The inverse function is ...

f^-1(x) = (4x +3)/(1 -x)

User Rodrigo Ortega
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.